Assessing Smart City’s Readiness in Semarang City for Sustainable Development - Badriah, Lilis Siti; Utami, Rian Dwi (Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
This study aims to analyze Semarang City's readiness to become a Smart City for sustainable development. This research employs qualitative analysis and utilizes secondary data from the mass media. The data were processed using Data Coding technique, Crosstab Queries, and Word Cloud Analysis. The result indicates that Semarang City has the potential for smart city development. It is supported by the implementation of flagship programs in Semarang City to achieve Smart City status, particularly in improving public services, creating a green environment, and fostering sustainable economic growth. Semarang City faces challenges such as inadequate supporting infrastructure for smart cities, disparities in technological know-how across society, and significant environmental challenges. Regarding implications, this study recommends that the municipal government undertake comprehensive development and training for the human resources involved in the Smart City initiative, in addition to providing technological outreach to the community to accelerate the Smart City initiative.